FAKTOR PENYEBAB RENDAHNYA HASIL BELAJAR GEOGRAFI SISWA KELAS VIII DI SMP N 31PADANG - susanti, Elva; Ahmad, Ridwan; Erita, Yeni (STKIP PGRI Sumbar, 2013)
Elva Susanti, (2013). Causes of Low Geography Student Learning Outcomes in Class VIII Â SMP N 31 Padang (Geography Education Program STKIP PGRI West Sumatera)This study aimed to obtain information, analyze and discuss data on the causes of learning outcomes of Geography lace eighth grade students in SMP N 31 Padang The type of research was descriptive correlational. The entire study population was in Junior High School Students in Padang totaled 31 227 people. The study sample in this study using a proportional system with random sampling so that the sample proportion of 30% amounting to 67 students. Based on a simple linear regression analysis, double (multiple) and the correlation it can be concluded as follows: (1) there is a relationship between attitudes to learning outcomes in geography class VIII SMP 31 Padang because t> t table (2.356> 1.671), low relationship strength (r = 0.280) and a very small contribution (7.9%), (2) There is a relationship between the discipline of geography learning outcomes at eighth grade students in SMP N 31 Padang for t> t table (2.093> 1.670), low-power relationship (r = 0.251) and a very small contribution (6.3%), (3) There is a relationship Between Facilities and Infrastructure With studentâs Learning Outcomes of Geography Class VIII in SMP N 31 Padang since t> t table (3.075> 1.670), the strength of the relationship being (r = 0.356) and a small contribution (12.7%) and (4) There is a Significant Relationship Between Studentâs attitude, Studentâs Discipline and Infrastructure together with the Geography Student Learning Outcomes in SMP N 31 Padang because Fhitung> F table (4.517> 2.751), the strength of the relationship between these three variables with Studentâs Learning Outcomes of Geography Class VIII in SMP N 31 Padang including moderate (r = 0.421) and a small contribution (17.7%)